Angiotensin II increases angiogenesis by NF‐κB–mediated transcriptional activation of angiogenic factor AGGF1. Issue 9 (11th April 2018) - Si, Wenxia; Xie, Wen; Deng, Wenbing; Xiao, Yi; Karnik, Sadashiva S.; Xu, Chengqi; Chen, Qiuyun; Wang, Qing Kenneth
ABSTRACT: Angiogenic factor with G‐patch and FHA domains 1 (AGGF1) is involved in vascular development, angiogenesis, specification of hemangioblasts, and differentiation of veins. When mutated, however, it causes Klippel‐Trenaunay syndrome, a vascular disorder. In this study, we show that angiotensin II (AngII)—the major effector of the renin–angiotensin system and one of the most important regulators of the cardiovascular system— induces the expression of AGGF1 through NF‐κB, and that AGGF1 plays a key role in AngII‐induced angiogenesis. AngII significantly up‐regulated the levels of AGGF1 mRNA and protein in HUVECs at concentrations of 10–40 μg/ml but not >60 μg/ml. AngII type 1 receptor (AT1R) inhibitor losartan inhibited AngII‐induced up‐regulation of AGGF1, whereas AT2R inhibitor PD123319 further increased AngII‐induced up‐regulation of AGGF1. Up‐regulation of AGGF1 by AngII was blocked by NF‐κB inhibitors, and p65 binds directly to a binding site at the promoter/regulatory region of AGGF1 and transcriptionally activates AGGF1 expression. AngII‐induced endothelial tube formation was blocked by small interfering RNAs (siRNAs) for RELA (RELA proto‐oncogene, NF‐κB subunit)/p65 or AGGF1, and the effect of RELA siRNA was rescued by AGGF1. AngII‐induced angiogenesis from aortic rings was severely impaired in Aggf1 +/ − mice, and the effect was restored by AGGF1. These data suggest that AngII acts as a critical regulator of AGGF1 expression through NF‐κB, and that AGGF1 plays a key role in AngII‐induced angiogenesis.—Si, W., Xie, W., Deng, W., Xiao, Y., Karnik, S. S., Xu, C., Chen, Q., Wang, Q. K. Angiotensin II increases angiogenesis by NF‐κB–mediated transcriptional activation of angiogenic factor AGGF1. FASEB J. 32, 5051–5062 (2018). www.fasebj.org